Thyrotropin stimulation of the ADP-ribosyltransferase activity of bovine thyroid membranes. - Vitti, P (1982)
Thyrotropin increases the ADP-ribosylation activity of bovine thyroid membranes. Rapid ADP-ribosylation of membrane components is followed by increasing ADP-ribosylation of components in the supernatant of the reaction mixture. One of the major membrane proteins ADP-ribosylated in the thyrotropin-stimulated reaction has an approximate molecular weight of 40,000; this same protein is also a major ADP-ribosylated product of the A promoter of cholera toxin and appears to be related to the G regulatory subunit of the adenylate cyclase complex. The ADP-ribosylated products appearing in the supernatant solution comigrate with thyrotropin and preparations of 125I-labeled alpha subunit of thyrotropin; the alpha subunit, but not the beta subunit, of thyrotropin can be ADP-ribosylated by the membrane ADP-ribosyltransferase activity. NAD can be shown to enhance the ability of thyrotropin to stimulate the adenylate cyclase activity of bovine thyroid membrane preparations and of membrane preparations of a rat thyroid tumor whose adenylate cyclase activity is otherwise unresponsive to thyrotropin. The beta subunit of thyrotropin inhibits thyrotropin stimulation of both the ADP-ribosylation and adenylate cyclase activities of the thyroid membrane.